Developing Area Level Socioeconomic Index for Risk Estimation Study of Cardiovascular Disease - Prof. Manoj.K.Sharma, Dr. Manjushri Sharma, Dr. Anurag Sharma (International Journal of Advanced Science and Technology, 2020)
Cardiovascular disease is fast becoming the leading cause of morbidity and mortality across the world, with developing countries bearing most of the brunt. India, with its burgeoning population, is facing a giant epidemic of CVD. The WHO Non communicable disease monitor report (2017) reveals that more than 60% of its mortality is because of non-communicable diseases (NCDs) (2) Amongst the NCDs, CVD alone accounted for 28.1% of total deaths and 14.1% of Disability adjusted life years in 2016(3)